Guía de evaluación para reestructuración de piscinas existentes - Santana-Sánchez, Cinthia (Instituto Tecnológico de Costa Rica, 2016)
The pool is currently building and restructuring whole field of action that involves various areas of engineering and whose views on how important they are diverse. The vessel is the structure that contains water, it supports both the water pressure and the soil that also surround the effects of buoyancy, seismic, potential settlements, etc. Leads the pipes so the water evenly for their returns and is returned to the pumping equipment is distributed, houses the skimmers and other accessories, has about it simple structures so that the activity of swimmers is given to the best . Keywords: pool, restructuring, process, evaluation, concrete.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Concreto; Cemento; ingeniería; Agua; construcción